Extensive calcification of the ligamentum flavum causing cervical myelopathy in a Caucasian woman - Roet, Milaine (Springerplus, 2016)
Calcification of the ligamentum flavum (CLF) can cause myelopathy due to spinal cord compression. Only several cases in Caucasian patients have been described. Neurological deterioration can only be stopped by surgical decompression. We report a 63-year-old Caucasian woman presenting with progressive pins-and-needles sensations in both hands, worsened by painful paresthesia in both lower extremities. MRI showed a dorsal compressive mass extending from C2 to Th3 vertebrae with myelopathy at the level of C6. A laminectomy was performed, which improved clinical symptoms. Histological examination showed CLF. Early recognition of CLF and early spinal cord decompression are needed to improve neurological outcome.